THE ROLE OF BEHAVIORAL NUDGES IN ENHANCING CEO DECISION-MAKING FOR INNOVATION - Safaâ Houna; Lena Lotta Sticken (PEOPLE: International Journal of Social Sciences, 2025)
This study examines the intersection of CEO influence on innovation and the potential of behavioural nudging techniques. It aims to develop a theoretical framework that applies principles from Nudge Theory and Upper Echelons Theory to enhance decision-making processes at the executive level, thereby fostering organisational innovation. The proposed framework identifies key decision points in the innovation process, where nudges such as default options, social norms, and framing effects can be effectively deployed to mitigate cognitive biases and promote innovation-focused choices. The study also addresses potential challenges, including ethical considerations and context-specific limitations, providing a comprehensive perspective on the application of nudges at the C-suite level. The academic contribution lies in bridging behavioural economics and innovation management, offering an evidence-based approach to improving strategic decisions. From an economic perspective, the framework elucidates how optimized decision-making processes can enhance competitiveness and drive innovation outcomes. Finally, the paper discusses practical implications for organisations and delineates directions for future empirical research, including longitudinal studies and real-world applications, to validate the proposed framework.